2015
DOI: 10.1210/jc.2014-3242
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Simultaneous Integrated Boost-Intensity Modulated Radiation Therapy for Patients with Locoregionally Advanced Papillary Thyroid Carcinoma: Preliminary Results of a Phase II Trial and Propensity Score Analysis

Abstract: Postoperative SIB-IMRT is feasible and effective in improving locoregional control in patients with locally advanced PTC. Large-scale randomized studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
0
18
0
6
Order By: Relevance
“…Local control of PTC with extrathyroid invasion is very important for avoiding macroscopic residual cancer either in locoregional or in distant metastasis [ 19 ]. In a recent study, with the help of technical advances in radiotherapy planning, simultaneous integrated boost intensity modulated radiotherapy was performed in patients with locoregionally advanced papillary thyroid cancer [ 20 ]. Preliminary results showed the method proved effective in improving locoregional control in patients with locally advanced PTC.…”
Section: Discussionmentioning
confidence: 99%
“…Local control of PTC with extrathyroid invasion is very important for avoiding macroscopic residual cancer either in locoregional or in distant metastasis [ 19 ]. In a recent study, with the help of technical advances in radiotherapy planning, simultaneous integrated boost intensity modulated radiotherapy was performed in patients with locoregionally advanced papillary thyroid cancer [ 20 ]. Preliminary results showed the method proved effective in improving locoregional control in patients with locally advanced PTC.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, recurrence was demonstrated pathologically by surgical resection or biopsy [16]. LFFS was defined as the time interval from the date of primary surgery to the date of local failure, death, or last contact, as appropriate.…”
Section: Methodsmentioning
confidence: 99%
“…LFFS was defined as the time interval from the date of primary surgery to the date of local failure, death, or last contact, as appropriate. Distant metastasis was defined as any recurrence outside of the cervical neck and the upper mediastinum [16]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At our center, 10-year recurrence rates of 22.2% in patients with pathologically negative lymph nodes and of 42.1% in those with pathologically positive lymph node metastases have been reported [5]. Although PTC has favorable overall survival outcomes, advanced pT and pN classifications predict higher rates of locoregional recurrence, and several studies have found evidence that the use of adjuvant RT decreased locoregional recurrences [6,7,8,9,10,11,12,13,14]. …”
Section: Introductionmentioning
confidence: 99%